Distributed agent-based building grey-box model identification. (August 2020) - Bäumelt, T.; Dostál, J.
Abstract: The paper deals with an identification (calibration) of a building thermal model as a crucial part of modern control algorithms. It describes a modelling issue and parameter identification approach. There is presented an identification approach using a so called dual decomposition method which decomposes a large optimization problem into smaller local ones which are then solved by local agents. The local models are found using a grey-box calibration and by a coordination of agents' mutual shared parameters a global consistency is obtained. The proposed method is tested on two examples; one is basically trivial, in the latter one, more complex, a model of a building simulated in the EnergyPlus program is obtained and offers promising results for (predictive) control-oriented purposes.